2016
DOI: 10.1186/s13063-016-1623-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a pharmacist-driven intervention in COPD (EPIC): study protocol for a randomized controlled trial

Abstract: BackgroundPatients with chronic obstructive pulmonary disease (COPD) are often nonadherent with medications and have poor inhaler technique. Community pharmacists can help to improve health-related quality of life and overall outcomes in patients with COPD. We aim to measure the effectiveness of a systematic, pharmacist-driven intervention on patients with diagnosed COPD.Methods/designThis pragmatic, parallel-group, cluster randomized controlled trial is designed to determine the effectiveness of a multifactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…Illiterate patients displayed less priority to self-care and being part of a minority group and having low income resulted in lesser ability to understand medical information and label instructions which lead to decreased adherence compared to literate patients. (11,12,13,14) Furthermore, our results suggests that socioeconomic status was significantly associated with adherence where lower socioeconomic group showed highest non adherence than other groups. In our study most patients were in the older population and required complex medications for various comorbid conditions which led to frustration and confusion and resulted in unintentional non adherence.…”
Section: Discussionmentioning
confidence: 67%
“…Illiterate patients displayed less priority to self-care and being part of a minority group and having low income resulted in lesser ability to understand medical information and label instructions which lead to decreased adherence compared to literate patients. (11,12,13,14) Furthermore, our results suggests that socioeconomic status was significantly associated with adherence where lower socioeconomic group showed highest non adherence than other groups. In our study most patients were in the older population and required complex medications for various comorbid conditions which led to frustration and confusion and resulted in unintentional non adherence.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have recognized the pharmacists' responsibility and role in education, counseling, prevention, and management of COPD [13,[16][17][18]. Interventions led by community pharmacists have been found to be beneficial on treatment outcomes in COPD patients according to international studies [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of a pharmacist to the formula has been tested in several countries (India, Canada, and Jordan). In fact, three randomized controlled trials [16][17][18] showed that pharmacy-led patient education can positively impact treatment outcome, COPD knowledge, medication adherence, quality of life, significant reduction in hospital admission rates, and emergency department visits [19].…”
Section: Introductionmentioning
confidence: 99%
“…A Canadian patient education project [27] covered adherence, inhalation techniques, health-related quality of life, and the use of health resources such as drug therapy and COPD exacerbations. Content included explanation of the current therapy, dosage, administration, patient expectations, duration of therapy, and potential outcomes, and follow-ups and improved inhaler use.…”
Section: Discussionmentioning
confidence: 99%